Thermophysical properties of seriguela pulp at different maturation stages (Research, Society and Development, 2020)
The present work aims to evaluate the thermophysical properties of the buttercup pulp (Spondias purpúrea L.) at different maturation stages through theoretical correlations. The seriguelas were classified according to their stage and maturation, manual pulping was performed, and the peel and pulp were used in the experiments and the seed was discarded. In the samples the water content, total solids and total soluble contents were determined, and through theoretical correlations the specific mass, thermal conductivity and specific heat were determined. There is a notable increase in the content of total soluble solids in the fruits when the maturation stage has advanced, ranging from 11.03 to 18.93 °Brix. The water content, total solids and total soluble solids of the buttermilk pulp showed a significant difference for the five different maturation stages. Thermophysical properties such as theoretical specific masses were influenced by the maturation stages and temperatures, while the thermal conductivity decreased with an increase in the maturation stage from 0.662 to 0.628 W/m °C. The specific heat decreased when there was an increase from stage I to V, that is, from 3.86 to 3.64 kJ/ kg °C, respectively.